2003
DOI: 10.1002/jbm.b.10024
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage and interfacial morphology of self‐etching adhesives in class V resin composite restorations

Abstract: The purpose of the study was to evaluate the marginal leakage of three adhesive systems in Class V resin composite restorations. Two adhesive systems containing acidic primers: Clearfil SE Bond (CSEB) and Etch & Prime 3.0 (E&P), were compared with a conventional water-based primer: Scotchbond Multipurpose Plus (SBMP). Class V cavities were made at the cementum-enamel junction of extracted human molars, which were then divided between three groups. One of the adhesive systems was applied to each group following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 24 publications
4
57
1
6
Order By: Relevance
“…32 Therefore, SBMP has been used in many studies as a reference adhesive for the enamel microleakage test. [17][18][33][34] CSEB (Group 1) also showed acceptable results on enamel margins. The PH-value of CSEB is 1.9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Therefore, SBMP has been used in many studies as a reference adhesive for the enamel microleakage test. [17][18][33][34] CSEB (Group 1) also showed acceptable results on enamel margins. The PH-value of CSEB is 1.9.…”
Section: Discussionmentioning
confidence: 99%
“…16 Several studies have shown that self-etching adhesives could seal enamel margins effectively. [17][18] Some studies reported that self-etching primer systems performed comparably to that of total-etch adhesive systems. 19 However, in other studies, self-etching adhesives showed greater scales of microleakage than adhesives using conventional phosphoric acid as the etchant.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been speculated about the possibility of an incomplete polymerization of adhesives within the hybrid layer [8,9], due not only to oxygen inhibition, but also to the presence of intrinsic water of the dentin, primer solvents or even to the existence of chemical incompatibilities between the components of the adhesives, specially when all-in-one systems are used [10,11]. To help with water (in dentin) and solvent (in the adhesive) evaporation, manufacturers recommend to gentle air-dry the treated tooth for a few seconds.…”
Section: Introductionmentioning
confidence: 99%
“…Carvalho et al [12] and Osorio et al [25] have reported that it is possible that the efficacy of a self-etching primer is not related only to pH level, but also may be caused by the presence, after curing, of unpolymerized acid monomers.…”
Section: Resultsmentioning
confidence: 99%
“…Infiltration assessment and measurement followed the scheme proposed by Osorio et al [25], which assigns a progressive score in accordance with the infiltration extent ( Table 1) (Fig. 2).…”
Section: Optical Microscopy and Microleakage Assessmentmentioning
confidence: 99%